Molecular Characterization of Aspergillus flavus Strains Isolated from Animal Feeds - Saber Hadjer; Chebloune Yahia; Moussaoui Abdallah (Polish Journal of Microbiology, 2022)
Aflatoxin (AF)-producing fungi such as Aspergillus flavus commonly contaminate animal feeds, causing high economic losses. A. flavus is the most prevalent and produces AFB1, a potent mutagen, and carcinogen threatening human and animal health. Aspergillaceae is a large group of closely related fungi sharing number of morphological and genetic similarities that complicate the diagnosis of highly pathogenic strains. We used here morphological and molecular assays to characterize fungal isolates from animal feeds in Southwestern Algeria. These tools helped to identify 20 out of 30 Aspergillus strains, and 15 of them belonged to the Aspergillus section Flavi. Further analyses detected four out of 15 as belonging to Aspergillus flavus-parasiticus group. PCR targeting the AF genes’ aflR-aflS(J) intergenic region amplified a single 674 bp amplicon in all four isolates. The amplicons were digested with a BglII endonuclease, and three specific fragments were observed for A. flavus but A. parasitucus lacked two typical fragments. Sequencing data of four amplicons confirmed the presence of the two BglII restriction sites yielding the three fragments, confirming that all four strains were A. flavus. In addition, this analysis illustrated the genetic variability within the A. flavus strains.